25-Hydroxyvitamin D, Vitamin D Binding Protein, Bioavailable 25-Hydroxyvitamin D, and Body Composition in a Diverse Sample of Women Collegiate Indoor Athletes - Jennifer B. Fields; Sina Gallo; Jenna M. Worswick; Deanna R. Busteed; Margaret T. Jones (Journal of Functional Morphology and Kinesiology, 2020)
Women athletes are at higher risk for bone diseases; yet, information on vitamin D status ((25(OH)D), vitamin D binding protein (VDBP), and bioavailable 25(OH)D is limited. Collegiate athletes (n = 36) from volleyball (WVB), basketball (WBB), and track and field (WTF) were measured for (25(OH)D), VDBP, and bioavailable 25(OH)D; body composition and bone mineral density (BMD); and skin pigmentation. Participants self-reported daily vitamin D intake and sun exposure. One-way analysis of variance analyzed mean differences in measures across sports. Linear regression examined relationships between 25(OH)D; VDBP; bioavailable 25(OH)D; and whole body, hip, and spine BMD. Participants’ (mean ± SD, 19.4 ± 1.4 years, 172.75 ± 8.21 cm, 70.9 ± 13.2 kg, and 22.9 ± 4.1% body fat) overall mean 25(OH)D was 70.5 ± 32.25 nmol/L, and 28% of participants were deemed inadequate and 61% below thresholds identified as sufficient for athletes. Although WBB athletes consumed higher (p = 0.007) dietary vitamin D (760.9 ± 484.2 IU/d) than WVB (342.6 ± 257.8) and WTF (402.3 ± 376.4) athletes did, there were no differences across sport in serum 25(OH)D. WVB and WTF had higher bioavailable 25(OH)D than WBB. No relationships existed between vitamin D status and body composition. Vitamin D inadequacy was identified among 1/3 of women indoor sport athletes. Consistent monitoring of vitamin D status and diet are recommended to sustain athlete health and sport performance.